The Mechanism and Pathways of Dopamine and Dopamine Agonists in Prolactinomas - Liu, Xiaoshuang; Tang, Chao; Wen, Guodao; Zhong, Chunyu; Yang, Jin; Zhu, Junhao; Ma, Chiyuan (Frontiers in Endocrinology, 2019)
Dopamine agonists (DAs) such as bromocriptine (BRC) and cabergoline(CAB) are the primary treatment choice for prolactinoma by inhibiting prolactin secretion and reducing tumour size. However, the mechanism of dopamine and DAs lead to the death of tumor cells are incompletely understood and some are even conflicting conclusions. The aim of this review is to summarize the different signaling pathways of dopamine and DAs in the treatment of prolactinomas to help better understanding of their functional and drug resistance mechanisms.